Exploring the role of two polypeptide nanofiber gels derived from RADA16-I self-assembly in accelerating burn wound healing - Congjing Song; Sijia Li; Chenyang Zhang; Jiale Li; Ming Li; Lianbao Ye; Weiqiang Chen (Scientific Reports)
Abstract This study systematically evaluates the therapeutic effects and molecular mechanisms of peptide nanofiber gels RG and RJ in deep second-degree burn wound healing. The gels are composed of the self-assembling peptide RADA16-I (R) conjugated with either a GLP-1 analog (G) or Jagged-1 protein (J), both of which exhibit good physicochemical properties, including well-defined three-dimensional nanofiber architectures, transparent gel consistency, and significantly enhanced mechanical strengths (storage modulus increased by ~ 4.3-fold for RG and ~ 7.09-fold for RJ) with high composite viscosities (5.36 Pa·s for RG; 7.08 Pa·s for RJ). In vitro experiments demonstrated that RG and RJ significantly promoted cell proliferation and migration. In vivo studies revealed that RG and RJ accelerated the healing of deep second-degree burn wounds through significant angiogenesis, reduction of systemic inflammation, and enhanced tissue regeneration. Notably, after 14 days, the wound closure rates in the RG and RJ groups reached 89.5% and 76.8%, respectively, compared to 70.1% in the R group and 67% in the control group. This difference can be attributed to their advantages in reducing systemic inflammation, promoting vascular formation during the healing process, and increasing collagen deposition. Our findings suggest that RG and RJ nanofiber gels hold great potential as innovative solutions for the care of deep second-degree burn wounds.